Does Green-Label Influence Green Purchase Intention, Attitude, Subjective Norms, Behavioral Control, and Willingness To Pay as Moderation? - Lukmawan, Wisnu Ridho; Wulandari, Ririn (Universitas Prasetiya Mulya, 2024)
The purpose of this study was to test and analyze influenced eco-labels, attitudes, subjective norms, and behavioral control on green purchase intention, as well as willingness to pay as a mediator to strengthen the influence green purchase intention (GPI) on green purchase behavior (GPB). The population of this study were Millennials and Gen Z who had purchased green products in Jabodetabek. The number of samples was 181 samples, determined based on Hair's Theory which allows for an unknown population. The sampling technique used nonprobability sampling and purposive sampling. Data analysis used the Least Square Partial Structural Equation Model (PLS-SEM). The results showed that eco-labels did not influence green purchase intention, but influenced green attitude and behavioral control. Conversely, ecolabels did not influence subjective norms. Furthermore, willingness to pay was unable to moderate the influence of green purchase intention on green purchase behavior.